The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/368637
|View full text |Cite
|
Sign up to set email alerts
|

FatalNocardia farcinicaBacteremia Diagnosed by Matrix-Assisted Laser Desorption-Ionization Time of Flight Mass Spectrometry in a Patient with Myelodysplastic Syndrome Treated with Corticosteroids

Abstract: Nocardia farcinica is a Gram-positive weakly acid-fast filamentous saprophytic bacterium, an uncommon cause of human infections, acquired usually through the respiratory tract, often life-threatening, and associated with different clinical presentations. Predisposing conditions for N. farcinica infections include hematologic malignancies, treatment with corticosteroids, and any other condition of immunosuppression. Clinical and microbiological diagnoses of N. farcinica infections are troublesome, and the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(24 reference statements)
1
3
0
2
Order By: Relevance
“…Because each Nocardia species shows a specific antimicrobial susceptibility pattern, reliable microbiological data is essential for selecting the initial antibiotic therapy. In our case, the results of species identification between MALDI-TOF mass spectrometry and molecular analysis were consistent with each other, indicating the usefulness of MALDI-TOF mass spectrometry [38] . A previous study demonstrated that N. farcinica species were relatively more resistant to multiple antimicrobial agents, including third-generation cephalosporins and aminoglycosides, except amikacin, clarithromycin, and minocycline, and susceptible to imipenem, linezolid, and amikacin [23] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Because each Nocardia species shows a specific antimicrobial susceptibility pattern, reliable microbiological data is essential for selecting the initial antibiotic therapy. In our case, the results of species identification between MALDI-TOF mass spectrometry and molecular analysis were consistent with each other, indicating the usefulness of MALDI-TOF mass spectrometry [38] . A previous study demonstrated that N. farcinica species were relatively more resistant to multiple antimicrobial agents, including third-generation cephalosporins and aminoglycosides, except amikacin, clarithromycin, and minocycline, and susceptible to imipenem, linezolid, and amikacin [23] .…”
Section: Discussionsupporting
confidence: 88%
“…In our case, the results of species identification between MALDI-TOF mass spectrometry and molecular analysis were consistent with each other, indicating the usefulness of MALDI-TOF mass spectrometry. [38] A previous study demonstrated that N. farcinica species were relatively more resistant to multiple antimicrobial agents, including thirdgeneration cephalosporins and aminoglycosides, except amikacin, clarithromycin, and minocycline, and susceptible to imipenem, linezolid, and amikacin. [23] Notably, the resistance rate of this species to trimethoprim/sulfamethoxazole was also approximately 50%; hence, an antimicrobial susceptibility test for trimethoprim/sulfamethoxazole is required, [22,23] although it has been selected as the first choice for empirical treatment in patients with nocardiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Species of Nocardia involved in human pathogenesis include Nocardia brasiliensis, Guinea pig nocardia and Picrax nocardia . Nocardiosis is a life-threatening disease ( 5 ) usually found in immunocompromised patients, or populations where it occurs secondary to other diseases. The lung is the most common site of nocardiosis, accounting for about 70–80% ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a soil saprophyte, Nocardia species invasion into human body through the respiratory tract, skin, or digestive tract. Nocardiosis usually prevalent in immunocompromised patients or affect the populations that secondary to other diseases, it is a life-threatening diseases to the infected patients [3] . Lung is the most commonly infective site of nocardiosis, accounting for about 70-80% [4,5] , Gsenkirchen nocca, Nocardia brasiliensis, Ginea pig ncardia and Picrax ncardia are the main pathogenic bacteria of Nocardia species frequently isolated from humans.…”
Section: Discussionmentioning
confidence: 99%